Multifunctional Shape‐Memory Polymer Foams with Bio‐inspired Antimicrobials. Issue 16 (28th December 2017) - Monroe, Mary Beth Browning; Easley, Alexandra D.; Grant, Katie; Fletcher, Grace K.; Boyer, Calla; Maitland, Duncan J.
Abstract: Despite a number of clinically available hemostats, uncontrolled bleeding is the primary cause of trauma‐related death. Shape‐memory polymer (SMP) foams have a number of desirable properties for use as hemostats, including shape recovery to enable delivery into bleed sites, biocompatibility, and rapid blood clotting. To expand upon this material system, the current work aims to incorporate phenolic acids, which are honey‐based antimicrobial agents, into SMP foams. We showed that cinnamic acid (CA) can be utilized as a monomer in SMP synthesis to provide foams with comparable pore structure and retained cytocompatibility. The addition of CA enabled tuning of thermal and shape‐memory properties within clinically relevant ranges. Furthermore, the modified foams demonstrated initial and sustained antimicrobial effects against gram‐positive and gram‐negative bacteria. These multifunctional scaffolds demonstrate potential for use as hemostats to improve upon current hemorrhage treatments and provide a new tool in tuning the biological and material properties of SMP foams. Abstract : Bee better : A honey‐based antimicrobial is incorporated into shape‐memory polymer foams to provide porous scaffolds for potential use in hemostatic wound treatment. The resulting foams have tunable, clinically relevant thermal properties, rapid shape recovery to enable shape‐filling of wounds, cytocompatibility, and efficacy against gram‐negative and gram‐positive bacteria to reduce infection risks.